Implementasi Peraturan Pemerintah Nomor 23 Tahun 2018 Tentang Pajak UMKM Di Desa Klambir Lima Kebun Kecamatan Hamparan Perak - Destari Nurlaila Damanik; Teuku Radhifan Syauqi; Adik Irma (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2024)
This study aims to analyze the implementation of Government Regulation No. 23/2018 on MSME Tax, which replaces the previous provision regarding the imposition of final tax on micro, small, and medium enterprises (MSMEs). This PP sets a tax rate of 0.5% of gross turnover, aiming to encourage taxpayer compliance and increase the contribution of MSMEs to state revenue. The research method used is a qualitative approach with data collection techniques through interviews, document studies, and observation. The focus of the analysis includes MSME taxpayers' understanding of this regulation, the level of tax compliance, and its impact on MSME business development. This research suggests the need for increased tax education for MSME players, strengthening the tax administration system, and continuous evaluation of policies to suit economic conditions and the needs of MSMEs.